Cultural Sensitivity in TESOL: A Key to Student Engagement - Dilorom Poyonova; Sevara Abdishukurova; Makhliyo Shomurodova (Scientific Trends, 2025)
Cultural sensitivity plays a crucial role in fostering inclusive, engaging, and effective English learning environments. This article explores the importance of cultural awareness in TESOL, offering strategies for integrating students' cultural backgrounds into lessons, addressing potential biases, and fostering a more inclusive classroom atmosphere.